Advances of Neoadjuvant Targeted Therapy in ALK-positive Non-small Cell Lung Cancer - Weizhen SUN; Yuheng ZHOU; Yaobin LIN; Shoucheng FENG; Hao LONG (Chinese Journal of Lung Cancer)
Lung cancer remains the most frequently diagnosed cancer and the leading cause of cancer-related death worldwide, with anaplastic lymphoma kinase (ALK) fusion mutations accounting for approximately 4%-9% of cases. In recent years, there are increasing clinical evidences suggesting that the combination of ALK inhibitors with surgical treatment holds significant potential for clinical application in resectable early and locally advanced non-small cell lung cancer (NSCLC) patients. This review aims to summarize the advances in neoadjuvant targeted therapy for ALK fusion positive NSCLC and discuss its advantages and challenges in clinical practice.